Applications and use of smart textiles and technology in equine science - Ternström, J.; Hawson, L.; Gunnarsson, E.; Engvall, T.; Karlsteen, M.; Sundin, M.; Berlin, L.; McLean, A.; McGreevy, P. (Embracing science to enhance equine welfare and horse-human interactions, 2013)
In a unique collaboration between Chalmers University, Gothenburg University, The Swedish school of Textiles, The Australian Equine Behavior Centre and the University of Sydney we are applying Smart Textiles to important questions in Equitation Science. Smart textiles enable measurement of a vast array of different variables with minimal interference. A prototype textile ECG gauge has been produced. Very promising capitative measurements have been made on humans with these electrodes and similar textile electrodes have been incorporated into a tight sweater measuring ECG resistively. Some measurements on horses have been done, but further development of the fastening of the electrodes has to be done to get more reliable and stable results. It is considered possible to in a near future include these sensors in the horses' normal equipment, such as the girth or saddle coat. This suggests possible applications in exercise physiology, hospital and stud. At the time of writing, capitative measurements on humans with a Signal to Noise Ratio of 16 have been made. The researchers are keen to improve measurement of the interaction between horse and rider through incorporation of the measurement devices into pre- existing equipment. Textile sensors for measuring pressure are under development. In contrast with other research in the same field using spacer fabric, we use only a thin three layer textile. This is unique and enables very thin and flexible applications. At the time of writing these textile sensors can measure a pressure difference of 6 g per sensor. By bringing together different branches of the sciences from physics to physiological psychology these researchers intend to apply modern materials science solutions to age old equine welfare questions. Layperson`s paragraph: The research demonstrates the applications of Smart Textiles in equine science. This use of Smart Textiles enables measuring tools for example ECG and pressure incorporated into the horses' normal equipment.